Local fractional similarity solution for the diffusion equation defined on Cantor sets. (September 2015) - Yang, Xiao-Jun; Baleanu, Dumitru; Srivastava, H.M.
Abstract: In this letter, the local fractional similarity solution is addressed for the non-differentiable diffusion equation. Structuring the similarity transformations via the rule of the local fractional partial derivative operators, we transform the diffusive operator into a similarity ordinary differential equation. The obtained result shows the non-differentiability of the solution suitable to describe the properties and behaviors of the fractal content.